A study of classical and quantum cosmology in modified teleparallel gravity and the role of Noether symmetry - Dipankar Laya; Shriton Hembrom; Sourav Dutta; Subenoy Chakraborty (European Physical Journal C: Particles and Fields)
Abstract The present work deals with Noether symmetry approach in a modified teleparallel gravity for classical quantum cosmological description. In the background of homogeneous and isotropic flat Friedmann–Lema $$\hat{\text{ i }}$$ i ^ tre–Robertson–Walker (FLRW) model, the Noether symmetry vector with the associated conserved charge identifies a cyclic variable so that the modified Einstein field equations get simplified and becomes solvable in the present model. In quantum cosmology, the operator version of the conserved associated momentum identifies the oscillatory part of the wave function and consequently it is possible to have the complete wave as the solution of the Wheeler–DeWitt (WD) equation. Finally, it has been examined whether classical singularity can be avoided or not by quantum description.